Fenomenologi Kepercayaan Sosial (Social Trust) dan Kerentanan Disinformasi pada Mahasiswa - Mario Fahmi Syahrial; Fera Dwidarti; Tri Mei Apta Arjanti (Paedagogie, 2026)
This study aims to uncover the process of constructing and interpreting social trust among PPKn students at Universitas PGRI Ronggolawe, as well as to analyze how the dimensions of social trust shape students' response patterns and evaluations of information received through social media. This study employed a qualitative approach with a phenomenological design grounded in post-positivist philosophy. Data were collected through semi-structured in-depth interviews, observation, and documentation involving five purposively selected third-semester students and one lecturer as a supporting informant. Data were analyzed using Creswell's six-step phenomenological analysis, ranging from the extraction of significant statements to the construction of essence descriptions, with data credibility ensured through source and technique triangulation. The findings reveal that students construct social trust through three mutually reinforcing dimensions: interpersonal trust that substitutes relational closeness for content verification, institutional trust that erodes through accumulated experiences of formal institutional inconsistency, and generalized trust that becomes distorted by algorithmic virality logic. This study concludes that students' vulnerability to disinformation is not merely a matter of insufficient digital literacy, but a structural problem rooted in the ways social trust is constructed and operationalized in everyday digital life.